The Correlation Between Family Support and Self Efficacy in Menstrual Hygiene Management Among Eleventh-Grade Girls at SMA N 1 Sidareja - Nuryati, Umi; Aprilina, Happy Dwi (UM Purwokerto Press, 2025)
Adolescence is a developmental stage where an individual progresses from the onset of secondary sexual characteristics to sexual maturity. During puberty, noticeable changes included rapid body growth, the appearance of secondary sexual characteristics, emotional fluctuations, and, most significantly for adolescent girls, the onset of menstruation. A lack of support from close family members in managing self-care during menstruation is a reproductive health issue that can lead to health disturbances. The purpose of this study was to determine the relationship between family support and self-efficacy towards menstrual hygiene management in female adolescents in grade XI of SMA N 1 Sidareja. This quantitative study was a cross-sectional correlational design. The study was conducted at SMA N 1 Sidareja from October 2023 to July 2024. The sample consisted of 105 eleventh-grade female students, selected using cluster random sampling followed by systematic random sampling. The research instruments included questionnaires assessing family support and self-efficacy in menstrual hygiene management Data were analyzed using the Chi-Square test. The Chi-Square test results indicated a significant correlation between family support and self-efficacy in menstrual hygiene management among adolescent girls at SMA N 1 Sida`reja (p-value = 0.005). This shows that there is a significant relationship between family support and self-efficacy towards menstrual hygiene management with a correlation that has a positive direction, meaning that the better the family support, the higher the self-efficacy towards menstrual hygiene management. It can be concluded that there is a significant correlation between family support and self-efficacy in menstrual hygiene management among eleventh-grade girls at SMA N 1 Sidareja.